2022
DOI: 10.1039/d2tc01626e
|View full text |Cite
|
Sign up to set email alerts
|

Covalent functionalization of few-layer TiS2 with tetraphenylporphyrin: toward a donor–acceptor nanohybrid featuring enhanced nonlinear saturation absorption

Abstract: Covalent functionalization of two-dimensional transition-metal dichalcogenides (TMDs) enables the manipulation of optical and electronic properties in hybrid structures and enhances their versatility for various potential applications. Herein, exfoliated few-layer TiS2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 85 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…5d provides insight into the Z-scan NLO performance, and Table S3 (ESI †) summarizes the linear and NLO parameters of all samples under the same pulse energy of 60 nJ in the fs regime of 800 nm. Remarkably, it has been found that charge transfer can occur on the fs time scale in heterostructures with strong electronic coupling, [7][8][9] but such NLO performance towards fs pulsed laser has not been reported in any MOF-based hybrids in the literature to date. Ti 3 C 2 QD/V 2 C PMOF heterostructure features a more pronounced RSA than a single component, as evidenced by a gradually decreased T min with the increase of input fluence from 20 to 60 nJ in Fig.…”
Section: Nlo Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…5d provides insight into the Z-scan NLO performance, and Table S3 (ESI †) summarizes the linear and NLO parameters of all samples under the same pulse energy of 60 nJ in the fs regime of 800 nm. Remarkably, it has been found that charge transfer can occur on the fs time scale in heterostructures with strong electronic coupling, [7][8][9] but such NLO performance towards fs pulsed laser has not been reported in any MOF-based hybrids in the literature to date. Ti 3 C 2 QD/V 2 C PMOF heterostructure features a more pronounced RSA than a single component, as evidenced by a gradually decreased T min with the increase of input fluence from 20 to 60 nJ in Fig.…”
Section: Nlo Propertiesmentioning
confidence: 99%
“…Nonlinear optical (NLO) materials play a pivotal role in various optical applications, such as optical limiting, optical switching, optical communications, and so on. [1][2][3] A wide range of materials has captured significant attention, including graphene, [4][5][6] transition metal sulfides, [7][8][9][10][11][12][13] black phosphorus, 14,15 perovskite, [16][17][18] polymers, 19,20 and MXene, [21][22][23][24][25][26] among others. Within these NLO materials, metal-organic frameworks (MOFs), [27][28][29] boasting tunable structures and diverse compositions, have emerged as ideal materials for NLO applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the b eff values of the SnS 2 /Por blend at 800 nm (323 cm G W À1 ) and 515 nm (409 cm G W À1 ) are slightly larger than those of SnS 2 nanosheets (220 cm G W À1 at 800 nm, 273 cm G W À1 at 515 nm) but much smaller than those of the SnS 2 -Por nanohybrid (945 cm G W À1 at 800 nm, 1582 cm G W À1 at 515 nm) at the same conditions, which may be due to a weaker connection and thus inefficient electronic interaction between SnS 2 nanosheets and tetraphenylporphyrin, and is also consistent with previous reports on the NLO absorption properties of covalently functionalized nanohybrids. [28][29][30][31] To gain a better understanding of the NLO behavior of the SnS 2 nanosheets and the SnS 2 -Por nanohybrid, an energy band model was proposed based on earlier reports of SnS 2 nanosheets and porphyrin. 46,59,60 As shown in Fig.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Covalent functionalization has shown promise as a means to tune the NLO properties of transition metal disulfides. [28][29][30][31] SnS 2 nanosheets can be modified via a simple hydrogen incorporation strategy and a one-pot functionalization strategy using L-glutatione, a sulfur source for solvothermal synthesis. 32,33 However, these strategies are not appropriate for functionalization with common organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Materials with extended p-conjugation have been elaborately designed and explored to pursue remarkable NLO performance. [4][5][6] The successful delamination of graphene [7][8][9] has prompted heightened interest in numerous two-dimensional (2D) materials within the realm of nonlinear optics, which encompass graphene derivatives, transition metal sulfides, [10][11][12][13][14][15][16] black phosphorus (BP), 17,18 and MXene. [19][20][21][22][23][24] However, distinct drawbacks hinder the potential of individual materials: graphene's inherent zero bandgap and limited modulation depth hamper its advancement in optoelectronic devices; the large bandgap of MoS 2 along with the narrow tunable bandgap range poses challenges in future devices; the air-instability of BP and perovskites is not ideal in practical developments.…”
Section: Introductionmentioning
confidence: 99%